(untitled) (Reflection and Critique Law Magazine, 2024)
The present work aims to observe the progress of technology, analyzing society and the legal system in all phases of the Industrial Revolution, until reaching Industry 4.0, since this is the central point of the biggest current deliberations. In this sense, it will discuss the civil liability of entities equipped with Artificial Intelligence, since they do not have legal personification, but can still perform acts similar to those of a human person. As well as, the application of Digital Law in cases where the problem is no longer with the entities or developers of this technology themselves, but with the people who make inappropriate use of Artificial Intelligence by Deepfake, contributing to disinformation, data manipulation, crimes against honor and even threats to the democratic state.